Joubert Syndrome: A Case Report - Kafle, Prakash; Shilpakar, Sushil Krishna; Sharma, Mohan Raj; Sedain, Gopal; Pradhanang, Amit K; Bhandari, Binod Raj (Nepal Journal of Neuroscience, 2018)
Joubert syndrome (JS) isa rare autosomal recessive neuro developmental disorder involving cerebellar vermis and brainstem, marked by agenesis of cerebellar vermis, ataxia, hypotonia, oculomotor apraxia, neonatal breathing problems and mental retardation. Magnetic Resonance Imaging (MRI) reveals the characteristic Molar tooth sign of midbrain and Batwing appearance of rostral fourth ventricle. Nepal Journal of Neuroscience 15:23-26, 2018